Remotely detuned receiver coil for high-resolution interventional cardiac magnetic resonance imaging - Marhabaie, Sina; Delcey, Marylène; El Hamrani, Dounia; Vaillant, Fanny; Ginefri, Jean-Christophe; Ozenne, Valéry; Abell, Emma; Poirier-Quinot, Marie; Quesson, Bruno (Frontiers in Cardiovascular Medicine, 2023)
Interventional cardiac MRI in the context of the treatment of cardiac arrhythmia requires submillimeter image resolution to precisely characterize the cardiac substrate and guide the catheter-based ablation procedure in real-time. Conventional MRI receiver coils positioned on the thorax provide insufficient signal-to-noise ratio (SNR) and spatial selectivity to satisfy these constraints. A small-dimension MRI receiver coil was developed and evaluated in experimental conditions. Anatomical images of the left ventricle at 170 µm in-plane resolution are provided on ex vivo beating heart from swine using a 2 cm circular receiver coil. Taking advantage of the increase of SNR at its vicinity (up to 35 fold compared to conventional receiver coils), the precision of real-time MR-thermometry imaging can reach a measured uncertainty below 0.1°C at the submillimetric spatial resolution. From the perspective of developing a therapeutic MR-compatible catheter equipped with an MRI receiver coil, we also propose methods to increase the safety of such devices by presenting an alternative remote active detuning technique of the receiver coil. Theoretical details are presented, together with simulations and experimental validation. The proposed approaches may also simplify the construction process and reduce the cost of such single-use devices. This study shows the potential of remotely decoupled small dimension surface coils for minimally invasive therapy of cardiac arrhythmia intraoperatively guided by MRI.